The Impact of Cyberwarfare on the National Security - Temur Digmelashvili (International Society of Philosophy and Cosmology, 2023)
Cyberwarfare has emerged as a critical threat to national security, encompassing attacks on critical infrastructure, government operations, and military capabilities. The increasing frequency and sophistication of cyberattacks necessitate effective strategies to mitigate this threat. Successful cyberattacks can disrupt essential services, cripple economies, and tarnish a nation's reputation. Attacks on military networks compromise classified information and communication systems, endangering military operations. Additionally, cyber espionage undermines national security by facilitating the theft of sensitive data. Moreover, cyber warfare can manipulate democratic processes, eroding public trust. To counter these threats, comprehensive cybersecurity strategies are vital, encompassing some specific defensive and offensive strategies that can be implemented to mitigate the threat of cyberwarfare. International cooperation and information sharing are essential for combating cyberwarfare and safeguarding national security. Addressing the impact of cyberwarfare requires a multifaceted approach to protect critical infrastructure, enhance military defenses, and preserve the integrity of democratic systems. The presented article discusses the factor of cyber war and its impact on national security, in the conditions of modern conflicts. The aim of the article is to demonstrate the impact of cyberattacks and cyberwar on national security.